STATUS REPRODUKSI DAN ESTIMASI OUTPUT KAMBING SABURAI DI DESA GISTING ATAS KECAMATAN GISTING KABUPATEN TANGGAMUS - Kusuma Adhianto; Siswanto Siswanto; Sulastri Sulastri; Anggi Derma Tungga Dewi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2019)
The goal of this study was to identify reproduction status, Natural Increase, Net Replacement Rate, and output estimation ofSaburai Goat in Gisting Atas village, Gisting subdistrict, Tanggamus regency. This research was conducted in March until April 2018. The material of this study is all of the Saburai goats which was available in the Gisting Atas Village, which number 89 heads. The results showed that the reproduction status of Saburai Goat in Gisting Atas Village were : first matingfor male goats was 15.47 months and for female goats was12.05 months, Post partum mating was for 2.67 months, calving interval was for 8.67 months. natural increase of Saburai goats was 24.72%, net replacement rate of male goats was 234.92%, and female goats was 121.62%, and the output Saburai goats was 24.72% (28 goats). Keywords: Reproduction Status, Natural Increase, Net Replacement Rate, Output Estimation, Saburai Goat